Growth performance of durian based on crop water requirement (ETc) using irrigation system - Fazlil Ilahi, Wan Fazilah; Rosdi, Nur Syaffiqa Izleen; Zulkapli, Muhammad Faris; Che’ Ya, Nik Norasma; Mat Su, Ahmad Suhaizi; Ping, Tan Ngai; Ramlee, Shairul Izan; Hock, Ong Choon (Universiti Malaysia Kelantan, 2024)
Water use for agricultural production in water scarcity regions requires precise irrigation water for sustainable irrigation management. The correct amount of irrigation water should be applied to ensure the survival of plants. Currently, farmers apply irrigation without considering the actual amount of the crop water requirement (ETc), which may lead to over or under-irrigation. These problems may cause water logging, crop stress, reduced yield and inefficient farm management. Durian (Durio zibethinus) is an important economic crop of Southeast Asian countries, including Thailand, Malaysia, and Indonesia. Lately, durian plantation has been increasing in Malaysia with innovative and sustainable approaches through irrigation or fertigation. The growth of durian is highly affected by water and nutrients given to the plants. This paper highlights the effect of precise irrigation through durian water requirement. Hence, this study aims to compare the difference in growth performance between existing practices (irrigation without ETc) and irrigation based on ETc. The study was conducted in the durian plantation at Sri Lalang, Kluang, Johor. There were two treatments tested on the durian, which are treatment 1 (T1) existing practice (irrigation without ETc) and treatment 2 (T2), irrigation based on ETc. The experimental design for this experiment is a Randomized Complete Block Design (RCBD) with four (4) blocks, and four trees for each treatment per block. The data collection includes the height of the tree, canopy width, girth’s diameter, node distance, leaf length and leaf weight. These data were analysed using ANOVA and LSD. Data was collected from April until November 2020. There was a significant difference in node distance from April until September. However, there were no significant differences for other growth parameters, suggesting precise crop water requirement can save water and minimize cost for the whole irrigation management.